PENGARUH SELF-AWARENESS DAN KREATIVITAS BELAJAR TERHADAP KEMANDIRIAN BELAJAR DALAM MATA PELAJARAN AKUNTANSI PADA SISWA JURUSAN AKUNTANSI SMK PAB 2 HELVETIA - Damanik, Melba; Ulfa Nurhayani; Dede Ruslan; Rini Herliani; Pasca Dwi Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education is essentially a planned and continuous process aimed at developing students’ potential to become independent, responsible, and competent individuals. However, the learning process in vocational schools, particularly in accounting subjects, still shows that many students rely heavily on teachers and have not yet developed optimal independent learning skills. This study aims to analyze the influence of self-awareness and learning creativity on learning independence in accounting subjects among students of the Accounting Department at SMK PAB 2 Helvetia. The research employed a quantitative approach using an ex post facto correlational method. The population consisted of students from the Accounting Department, with a sample of 41 students selected as research respondents. Data were collected through a Likert-scale questionnaire based on indicators of self-awareness, learning creativity, and learning independence. The data analysis technique used multiple linear regression analysis with the assistance of the Statistical Package for the Social Sciences (SPSS) version 26. The results of the study indicate that self-awareness has a positive and significant effect on students’ learning independence with a regression coefficient of 0.659 and a significance value below 0.05. Furthermore, learning creativity also shows a positive and significant influence on learning independence with a regression coefficient of 0.686 and a significance value below 0.05. Simultaneously, self-awareness and learning creativity contribute positively to strengthening students’ learning independence. These findings suggest that improving students’ awareness of their own learning potential and encouraging creative learning strategies can enhance independent learning behavior in accounting education.